EFFECTIVE APPROACHES TO COMPLEX ASSESSMENT OF THE LEVEL OF PSYCHOPHYSIOLOGICAL ADAPTATION OF PUPILS AND STUDENTS - Serheta , Ihor (Collection of scientific papers «ΛΌГOΣ», 2024)
In the course of research carried out in recent years scientifically based methods of complex assessment of the features of the course of psychophysiological adaptation of pupils and high school students and in the conditions of the implementation of stressful everyday activities in modern general education and higher educational institutions, which provide an opportunity to determine the features of the course of adaptation processes of young women and young men to the conditions of carrying out intense everyday educational activities, as well as justifying fully adequate to the requirements of the individual individualized strategies for the use of preventive means of psychophysiological influence and psychohygienic correction of existing negative shifts [1, 2, 3]. The developed methods provide for establishing the features of the processes of formation of the leading correlates of psychophysiological adaptation and, therefore, determining the level of development of psychophysiological functions (speed of simple and differentiated visual-motor reaction, mobility and balance of nervous processes, critical frequency of fusion of light flashes, coordination of movements, etc), which determine a high level of psychophysiological readiness of school-aged pupils and students to carry out effective educational activities in the conditions of modern educational institutions, adequate assimilation of theoretical knowledge and practical skills [4, 5, 6, 7].